Benefit of Noni Fruit (Morinda citrifolia) Extract in Reducing SGOT and SGPT Levels in Male White Rats (Rattus norvegicus) Induced by Doxorubicin - Ainaka Fatihi Gusmardi; Diah Purwaningsari; Anang Mufti Sumarsono (Universitas Airlangga, Surabaya, Indonesia, 2026)
Background: Drug-related hepatic injury, recognized as drug-induced liver injury (DILI), constitutes a significant global cause of acute hepatic damage, often resulting from exposure to conventional medications or traditional herbal remedies. Morinda citrifolia, a tropical fruit rich in antioxidants, offers potential hepatoprotection against oxidative stress induced by agents such as doxorubicin. Oxidative stress plays a central role in doxorubicin-induced hepatocellular damage, highlighting the need for adjunctive protective strategies. Objective: To evaluate whether Morinda citrifolia fruit extract could exert a hepatoprotective effect in male Wistar rats (Rattus norvegicus) subjected to doxorubicin-induced liver injury by measuring serum SGOT and SGPT levels. Materials and Methods: In this controlled post-intervention laboratory experiment, the authors classified 32 male Wistar rats into four groups (n = 8 per group): C− (standard diet only); C+ (intraperitoneal doxorubicin 20 mg/kg BW with a standard diet); CT1 (intraperitoneal doxorubicin 20 mg/kg BW followed by oral Morinda citrifolia extract at 500 mg/kg BW); and CT2 (intraperitoneal doxorubicin 20 mg/kg BW followed by oral Morinda citrifolia extract at 1000 mg/kg BW). The rats were sacrificed after 6 days and blood analysis was performed. Results: Blood analysis revealed significant different SGOT and SGPT levels between groups. Mean SGOT levels decreased significantly in CT1 versus C+ (P = 0.042) and CT2 versus C+ (P = 0.008). Mean SGPT levels declined in CT1 compared with C+ (P = 0.003) and CT2 compared with C+ (P = 0.002). Conclusion: Morinda citrifolia fruit extract at 500 and 1000 mg/kg BW effectively lowers doxorubicin-elevated SGOT and SGPT levels, indicating hepatoprotective potential.